ESTRUTURA DESCRITIVA DE SISTEMAS URBANOS NA REVISÃO DO PLANO DIRETOR DE MOGI DAS CRUZES - Fujimori, Maria Izabel Bonafe; Abiko, Alex Kenya (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
A city is a system of systems, which interacts with each other directly or indirectly. From the point of view of sustainable urban development, the sustainable cities need to improve the use of infrastructures by overlapping their uses. To ensure a better quality of life for its citizens, there is a need to further the integration of systems. In this way, the objective of this work is to propose a strategy to organize this structure in its different levels and to enable the measurement of the attentive goals and to propose goals for cities, regardless their characteristics. The method was applied to the case study of the municipality of Mogi das Cruzes. Finally, we seek to contribute to the issue of municipal organization in establishing a descriptive structure for the analysis of indicators that are ancillary to the government searching for sustainable cities.